Ã¢â‚¬Å“Monolingual or Bilingual Approach?Ã¢â‚¬Â The Best Approach to Teach Speaking for Beginner Level - Yuliyanto Sabat; Aulia Kususma Wardhani (JET ADI BUANA, 2018)
Some English teachers argue that the use of monolingual approach or Ã¢â‚¬Å“English OnlyÃ¢â‚¬Â gives a lot of exposures to students and some others report it just makes the students reluctant to speak as they understand nothing about the topics being discussed. Considering the important roles of teaching approaches on studentsÃ¢â‚¬â„¢ success to use English, it is very crucial to conduct a research on this topic. This article is an attempt to report which approach students like the most either Ã¢â‚¬Å“English OnlyÃ¢â‚¬Â or bilingual approach in learning speaking. Besides, it also reveals the reasons why the students choose one of the teaching approaches. As the researcher teaches speaking for beginner level, he uses his students as the subject to facilitate him to collect the data. He uses qualitative research method by using interview, questionnaire, and classroom observation to collect the data. The result of this research showed that studentsÃ¢â‚¬â„¢ negative perception on the use of English only and positive perception on the use of code switching supported by the result of questionnaire 95.65% participants chose strongly agree for code switching as their preferable teaching approach with the most common reasons on the material comprehension (86.86% strongly agree) and building self- confidence (78.26% strongly agree). Keywords: monolingual approach, bilingual approach, classroom interaction